Emotion recognition deficits among persons with schizophrenia: Beyond stimulus complexity level and presentation modality. (30th June 2016) - Feingold, Daniel; Hasson-Ohayon, Ilanit; Laukka, Petri; Vishne, Tali; Dembinsky, Yael; Kravets, Shlomo
Abstract: Studies have shown that persons with schizophrenia have lower accuracy in emotion recognition compared to persons without schizophrenia. However, the impact of the complexity level of the stimuli or the modality of presentation has not been extensively addressed. Forty three persons with a diagnosis of schizophrenia and 43 healthy controls, matched for age and gender, were administered tests assessing emotion recognition from stimuli with low and high levels of complexity presented via visual, auditory and semantic channels. For both groups, recognition rates were higher for high-complexity stimuli compared to low-complexity stimuli. Additionally, both groups obtained higher recognition rates for visual and semantic stimuli than for auditory stimuli, but persons with schizophrenia obtained lower accuracy than persons in the control group for all presentation modalities. Persons diagnosed with schizophrenia did not present a level of complexity specific deficit or modality-specific deficit compared to healthy controls. Results suggest that emotion recognition deficits in schizophrenia are beyond level of complexity of stimuli and modality, and present a global difficulty in cognitive functioning. Highlights: Participants without schizophrenia exhibited higher recognition accuracy across all modalities when compared to participants with schizophrenia. Recognition accuracy for visual stimuli was higher than for auditory stimuli but lower than the recognition rate of semantic stimuli. Difference in recognition rate between individuals with and without schizophrenia was greater for low- compared to high-complexity stimuli.